Philosophical and Sociological Background of the Integration of Religion and Science - Masruroh, Nunung; Amril M, Amril M (Kayon Media, 2025)
This research discusses the philosophical and sociological background behind the integration of religion and science, which have often been viewed as opposing entities. Using a literature review method, the study finds that this integration is driven by postmodernist thought as a response to the failure of modernism, which overly emphasizes positivism and empiricism. Philosophically, the integration is based on a holistic ontological view of reality, pluralistic epistemology, and axiology that promotes values beneficial for both worldly and spiritual life. Sociologically, it arises in response to modernization, secularization, a crisis of meaning, and society’s need for comprehensive education. In conclusion, the integration of religion and science is not merely an academic approach but a philosophical and social necessity for building an intellectually and spiritually balanced society.